First Principles Investigation of SrBi2Ta2O9 - Stachiotti, Marcelo Gabriel (2000)
The electronic structure of SrBi2Ta2O9 (SBT) is investigated from first-principles, within the local density approximation, using the full-potential linearized augmented plane wave (LAPW) method. The results show that, besides the large Ta(5d)-O(2p) hybridization which is a common feature of the ferroelectric perovskites, there is an important hybridization between bismuth and oxygen states. The role played by these two covalent bonds for driving the ferroelectric instability in SBT is investigated.